Simulation of biomass and/or coal gasification systems integrated with fuel cells - ÖZDOĞAN, ZEYNEP SİBEL (ASME, 2006)
This paper presents the results of a system simulation study. The HYSYS 3.1 - ASPEN code has been used for simulation. The system consists of a fixed bed gasifier followed by reforming and clean-up units. The produced hydrogen gas is fed to a PEM fuel cell. The gasified hydrocarbons are hazelnut shells, bark, rice straw, animal waste, and two lignites. Hydrocarbon properties, gasification, and reforming process parameters all affect the system efficiency. The effect of the moisture content and oxygen to carbon ratio of the hydrocarbon fees on the fuel processing and overall system efficiencies are presented. The overall efficiency of the system increases with increasing hydrocarbon feed oxygen to carbon ratio; this tendency is more evident at higher moisture levels.
Keywords: biomass; gasification; PEMFC